Exchange rate pass-through import prices: sectoral analysis - Duasa, Jarita; Ahmad, Nursilah (SAGE Publications Pvt. Ltd, 2011)
This study examines the pass-through effects of exchange rate changes on the import prices in Malaysia by commodity sections at one digit level. In methodology, the study adopts vector error correction (VECM) model using monthly data of nominal exchange rates, money supply and prices of imports by section, covering the period of M1:1999 to M12:2006. For further analysis, we adopt an innovation accounting by simulating impulse response functions (IRF). Cumulative IRF is then used to calculate the exchange rate pass-through on import prices in each commodity. The findings indicate that, while the exchange rate shock is significantly affect the fluctuation of import prices of foods, beverages, crude materials inedible, chemicals and manufactured goods, the degree of pass-through is incomplete. The findings reflect that exchange rate pass-through is endogenous to Malaysian inflationary environment and monetary policy credibility.